AN INTRODUCTION TO TRADITIONAL GAMES AS A MEDIUM FOR STRENGTHENING CULTURAL IDENTITY IN EARLY CHILDHOOD AT KARTIKA XVII-18 KINDERGARTEN PALANGKA RAYA - Ade Yusuf Ferudyn; Stefani Ratu Lestariningtyas; Yulina Mingvianita; Jumadi; Rahayu Auliyana Fitri; Metra (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
Preserving traditional games is crucial to maintain cultural values and national identity, which are being threatened by technological developments and modern games. Traditional games are not just an entertainment, but also a platform for learning social and cultural values such as cooperation, honesty, and tolerance, which are essential for children's motor, cognitive, and character development. Therefore, introducing and preserving traditional games for early childhood is a strategic way to maintain cultural heritage and support their holistic development. This community service was addressed to Kartika XVII-18 Kindergarten in Palangka Raya where traditional games have not been explicitly integrated into learning activities. The local cultural content that students learn is still limited to artistic aspects such as traditional Dayak dances for ceremonial purposes and competitions. Meanwhile, implementing traditional games in the school environment is also hampered by the lack of supporting facilities for applying traditional games in learning activities. This community service was held with a participatory approach and hands-on learning through stages of socialization of traditional games, demonstrations, practice of traditional games by children, and joint evaluation/reflection which involves children and teachers actively. This activity is expected to overcome the partner's problems as well as supporting